2021
DOI: 10.1038/s41598-021-86360-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive characterization of complex coronary lesions

Abstract: Conventional invasive diagnostic imaging techniques do not adequately resolve complex Type B and C coronary lesions, which present unique challenges, require personalized treatment and result in worsened patient outcomes. These lesions are often excluded from large-scale non-invasive clinical trials and there does not exist a validated approach to characterize hemodynamic quantities and guide percutaneous intervention for such lesions. This work identifies key biomarkers that differentiate complex Type B and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Taylor et al have suggested that the total microvascular resistance at hyperemic condition reduces up to 24% of the healthy value 53 , 55 . Recently, Randles et al have used a 25% reduction in microvascular resistance at hyperemic condition compared with the normal one 54 .…”
Section: Methodsmentioning
confidence: 99%
“…Taylor et al have suggested that the total microvascular resistance at hyperemic condition reduces up to 24% of the healthy value 53 , 55 . Recently, Randles et al have used a 25% reduction in microvascular resistance at hyperemic condition compared with the normal one 54 .…”
Section: Methodsmentioning
confidence: 99%
“…ML models have been used to automatically segment medical images for creating 3D computer models in recent years. Especially in patient−specific biomechanical modeling, each cardiovascular disease leads to multi−feature 3D morphologies, such as atherosclerosis [ 94 ], aneurysm [ 95 ], and occlusive diseases [ 96 , 97 ]. For instance, Berhane et al [ 98 ] used deep learning to generate an automatic 3D segmentation model of the aorta based on 4D−flow magnetic resonance imaging (MRI).…”
Section: Application Of Artificial Intelligence In the Prediction Of ...mentioning
confidence: 99%
“…Two key approaches are known to determine the boundary conditions. The first one involves predicting conditions based on models of the [19,20], also known as Windkessel models [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The first one involves predicting conditions based on models of the arterial system. The most popular are lumped models [19,20], also known as Windkessel models [2123].…”
Section: Introductionmentioning
confidence: 99%